2019
DOI: 10.1071/cp16316
|View full text |Cite
|
Sign up to set email alerts
|

Ability of sulfur-oxidising bacteria to hasten degradation of ground rubber particles in soil for release of zinc as a fertiliser to correct deficiency in wheat

Abstract: Previous research has shown that ground rubber from tyres can be used to supply fertiliser zinc (Zn) for prevention of Zn-deficiency in crops, and that inoculation of the ground rubber with several bacterial species hastens the release of Zn to the soil. We evaluated the ability of several microbial combinations to speed the release of Zn from ground rubber and to decrease soil pH to favour phytoavailability of Zn to crops. In a batch experiment, treatment combinations of two rates of ground crumb rubber (nil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The increase in plant growth in the TWP and Pseudomonas strains treatments can be attributed to the effects of TWP (as a source of Zn and Fe) and the diverse plant growth-promoting properties of Pseudomonas strains such as nutrient solubilization (via exudation of organic acid anions), producing indole-3-acetic acid (IAA), as well as improving plant stress tolerance by exuding ACC deaminase (Azarmi et al 2016). These ndings are in accordance with the results of Asadollahzadeh et al (2019) who reported that the application of sulfuroxidizing bacteria was effective in increasing wheat biomass in a TWP-treated soil.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The increase in plant growth in the TWP and Pseudomonas strains treatments can be attributed to the effects of TWP (as a source of Zn and Fe) and the diverse plant growth-promoting properties of Pseudomonas strains such as nutrient solubilization (via exudation of organic acid anions), producing indole-3-acetic acid (IAA), as well as improving plant stress tolerance by exuding ACC deaminase (Azarmi et al 2016). These ndings are in accordance with the results of Asadollahzadeh et al (2019) who reported that the application of sulfuroxidizing bacteria was effective in increasing wheat biomass in a TWP-treated soil.…”
Section: Discussionsupporting
confidence: 92%
“…Thiobacillus ferrooxidans and T. thioparus were shown to break the S-S bonds at the surface of rubber particles (Chritiansson et al 1998;Li et al 2011). Asadollahzadeh et al (2019) demonstrated that inoculation of TWP with some PGPR strains (Rhodococcus erythropolis, Acinetobacter calcoaceticus, Pseudomonas putida P41, Thiobacillus spp) led to a signi cant decrease in soil pH and therefore increased Zn bioavailability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation